Effect of Family Training on Profitability of Small-Scale Broiler Farming in Joypurhat District - Islam, M S; Islam, M N; Khatun, H; Faruque, S; Afroz, M A; Alam, M A (The Agriculturists, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> This study was conducted to compare the productivity and profitability of trained and non-trained small-scale broiler farmers in the Joypurhat district of Bangladesh. A total number of sixty farmers were trained on the modern techniques for profitable and sustainable broiler farming. The study showed that the mortality of broiler was 2.90±0.89 percent and 11.30±2.29 percent for trained and non-trained farmers, respectively (P<0.001). Feed conversion ratio (FCR) was 1.65±0.08 and 1.75±0.10 for trained and non-trained farmers, respectively (P<0.01). The net profit was 18.60±2.77 and 8.74±2.05 taka per broiler for trained and non-trained farmers, respectively (P<0.001). It can be concluded from the present study that the family training would be a very essential tool for gaining more productivity and profitability of small scale broiler farming in Bangladesh. <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014; 12(2) 137-141 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>